Theater im Gespräch Sprachliche Publikumspraktiken in der Theaterpause - Gerwinski, Jan (De Gruyter, 2018)
Conversation in the theatrical break is traditionally associated with the ideal of a public which, inspired by the previous stage experience, rhetorically skillfully communicates about aesthetic and socio-political issues. On the other hand, it is assumed from a critical perspective that such conversations primarily served social distinction, with a banal content. This study empirically reconstructs the practices characteristic of such situations between art communication and recreation, sociability and informal learning on a conversational basis.